Contribution of Self Concept Clarity to Online Self Presentation Among Users of Anonymous Accounts on Social Media - Wuri Handayani Suwandi; Mardianto Mardianto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Individuals have the chance to show themselves in a different way through online self presentation. When people have a clear self concept, they are more likely to express themselves online in a way that is consistent with who they are. People can experiment with their identities by using anonymous accounts on social media, which gives them more freedom to express themselves without worrying about unfavorable social reactions. The purpose of this study is to ascertain how self concept clarity affects people who express themselves online, especially those who use anonymous social media accounts. A quantitative approach to data analysis utilizing basic linear regression is the research methodology employed. 162 individuals who completed a Google Forms questionnaire made up the sample. The Self Concept Clarity Scale and the Presentation of Online Self Scale (POSS) were the scales employed in this investigation. With the regression equation Y=80.154-0.757X, the results demonstrate that self-concept clarity strongly contributes in a negative direction to online self-presentation by 19.4% (R²=0.194, p=0.000<0.05). This shows that the more uncertain or low the clarity of an individual's self, the greater the individual's tendency to build a new image or persona so that the online self presentation behavior shown is higher.